2015
DOI: 10.1002/ange.201503916
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Oxidation: Formyl CH Bond Activation by the Surface Lattice Oxygen of Regenerative CuO Nanoleaves

Abstract: An integrated experimental and computational investigation reveals that surface lattice oxygen of copper oxide (CuO) nanoleaves activates the formyl CH bond in glucose and incorporates itself into the glucose molecule to oxidize it to gluconic acid. The reduced CuO catalyst regains its structure, morphology, and activity upon reoxidation. The activity of lattice oxygen is shown to be superior to that of the chemisorbed oxygen on the metal surface and the hydrogen abstraction ability of the catalyst is correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…In the transition state, one H atom of water molecule is transferred to the hydroxyl OH group of phenylethanol facilitating the dehydroxylation, while the surface H adsorbed in Pd surface is transferred to the water molecule simultaneously in the concerted mechanism. This type of water mediated H-shuttling mechanism has also been reported in literature for the water-assisted dehydroxylation from HCOH on Ru catalyst, 52 CO hydrogenation of adsorbed CO on Co(111) surface, 53 formyl C-H dissociation glucose on CuO catalyst 54 and dehydroxylation of carboxylic acids on Pd(111) surface. 27 It is important to mention that this type of H-shuttling reaction usually suffer from extra entropic energy penalty for locating the water molecule to the exact position in the transition state (computed to be ~55.4 kJ/mol at reaction temperature of 60 o C in this study), as was also reported by Gunasooriya et al 53 and Amaniampong et al 55 This entropic penalty therefore increases the total barrier for the Hshuttling reaction to ~142 kJ/mol, making it further less favourable compare to the direct dehydroxylation pathway (124 kJ/mol, Figure 6 & 7k).…”
Section: Role Of Ph-pop Frame Structure In Facilitating the Formation Of Ethylbenzne (Eb)supporting
confidence: 79%
“…In the transition state, one H atom of water molecule is transferred to the hydroxyl OH group of phenylethanol facilitating the dehydroxylation, while the surface H adsorbed in Pd surface is transferred to the water molecule simultaneously in the concerted mechanism. This type of water mediated H-shuttling mechanism has also been reported in literature for the water-assisted dehydroxylation from HCOH on Ru catalyst, 52 CO hydrogenation of adsorbed CO on Co(111) surface, 53 formyl C-H dissociation glucose on CuO catalyst 54 and dehydroxylation of carboxylic acids on Pd(111) surface. 27 It is important to mention that this type of H-shuttling reaction usually suffer from extra entropic energy penalty for locating the water molecule to the exact position in the transition state (computed to be ~55.4 kJ/mol at reaction temperature of 60 o C in this study), as was also reported by Gunasooriya et al 53 and Amaniampong et al 55 This entropic penalty therefore increases the total barrier for the Hshuttling reaction to ~142 kJ/mol, making it further less favourable compare to the direct dehydroxylation pathway (124 kJ/mol, Figure 6 & 7k).…”
Section: Role Of Ph-pop Frame Structure In Facilitating the Formation Of Ethylbenzne (Eb)supporting
confidence: 79%
“…High resolution TEM image (cf. Figure 1c) showed a clear and continuous lattice fringe with an interfringe d spacing of 0.234 nm (inset in Figure 1c), characteristic for the [111] plane distance of monoclinic CuO 5,11 In agreement with SEM and TEM measurements, N 2 adsorption−desorption experiments (Supporting Information, cf. Figure S1) showed a type II isotherm with a type H 3 hysteresis loop attributed to macroporous material (according to the IUPAC classification) and corresponded to the formation of plate-like particles.…”
Section: Catalyst Synthesis and Characterizationsupporting
confidence: 78%
“…80-1917), with dominating peak at 2θ = 38.6 and 35.58°, which are characteristics for CuO(111) and CuO(−111) surfaces, respectively. 4,5,11 The morphology of the as-synthesized CuO was studied using scanning electron microscope (SEM). A uniform leaf-like morphological structure (cf Figure 1b) was observed, which was strikingly consistent with the low magnification transmission electron microscopy (TEM) image (inset in Figure 1b).…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of CuO catalysts including CuO nanoleaves, 53 CuO microspheres, 54 CuO/TiO 2 , CuO/HAP, and CuO/CeO 2 were prepared and evaluated (XRD data shown in Figure S12). Over a CuO/TiO 2 catalyst and 5 bar of O 2 gas, 35.3% HAc was obtained within 60 min even when the CuO amount was reduced by a factor of 10, highlighting the potential for catalyst design (Table S4).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%